용사코팅용 나노 WC-12Co 피드스톡의 제조 - 전형우; 김주선; 박주영; 박종구; 황순영; 이해원 (대한금속·재료학회, 2004)
This study investigates the fabrication of WC-12Co feedstock powders with weakly flocculated slurries by spray drying under various conditions. The morphological defects and flocculation states according to the amount of additives are evaluated to prepare spherical WC-Co feedstock powders with little morphological defects and homogeneous microstructures. The characteristics of feedstock powders, heat treated between 850~1200oC, are analyzed via SEM, EPMA, and mercury porosimetry. The results showed that with the increase in heat treatment temperature the portion of larger pores around 10 mm increased while, that of smaller pores of 1 mm lessened due to the coalescence of WC particles, forming dense feedstock powders with little defects such as hollow or craters. The feedstock heat treated at 1200oC showed a porosity of 42.2% and a density of 8.28 g/cm3 as well as uniform distribution of pores and Co.